Community of the Transfiguration : the journey of a new monastic community - Dekar, Paul R. (New monastic library., 2008)
In the 1930s, German theologian Dietrich Bonhoeffer anticipated the restoration of the Church after the coming Second World War through a new kind of monasticism, a way of life of uncompromising adherence to the Sermon on the Mount in imitation of Christ. Since then, the renewal of Christian monasticism has become a great spiritual movement. Imbued with a love for God and neighbor, and with a healthy self-love, people are going to monasteries to deepen their relationship with God, to pray, and to find peace. While some monastic institutions are suffering a decline in traditional vocations, man.